Analisis Teks Prosedur Siswa Kelas XI SMK Negeri 6 Padang - Yefrizon; Najmi Hayati; M. Kohir (JURNAL ARMADA PENDIDIKAN, 2023)
This study aims to describe (1) the accuracy of students’ procedural text structure and (2) inaccuracies in structure, writing, and meaning in procedural texts produced by eleventh-grade students at SMK Negeri 6 Padang. The study employed a qualitative approach using a descriptive method. The data consisted of 25 student procedural texts collected through document analysis. The researcher served as the primary instrument. Data analysis followed qualitative procedures: data reduction, data display, and verification. The results show that students’ texts contained the three essential components of procedural text structure: goal, steps (instructions), and reaffirmation (closing). In addition, accuracy was found to be more dominant than inaccuracy in both writing and meaning, although writing errors were still identified in some texts. Recommendation: instruction on procedural texts should emphasize editing practice (spelling, word choice, and sentence clarity) and strengthening the semantic alignment of each step so that structurally complete texts are consistently accompanied by linguistic accuracy and clear meaning.